2009
DOI: 10.1086/605023
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Memory Response to Pneumococcal Protein Antigens in an Area of High Pneumococcal Carriage and Disease

Abstract: In this population, T cell-mediated immunological memory potentially capable of pathogen clearance and immune surveillance is common but is not associated with the absolute interruption of pneumococcal carriage. How this naturally acquired immune memory influences pneumococcal vaccine efficacy remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 47 publications
5
55
2
Order By: Relevance
“…In fact, we have previously shown that, while pneumolysin triggers IL-1␤ secretion in murine DCs, it inhibits IL-1␤ in human DCs (15). Furthermore, in agreement with our study, Mureithi and colleagues found that, although recombinant pneumolysin could induce IFN-␥ and IL-17 from human PBMCs, the responses seen with the wild type and a pneumolysin-deficient mutant did not differ (25).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In fact, we have previously shown that, while pneumolysin triggers IL-1␤ secretion in murine DCs, it inhibits IL-1␤ in human DCs (15). Furthermore, in agreement with our study, Mureithi and colleagues found that, although recombinant pneumolysin could induce IFN-␥ and IL-17 from human PBMCs, the responses seen with the wild type and a pneumolysin-deficient mutant did not differ (25).…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, Kemp et al found that IFN-␥-producing T cells disappear from the circulation in patients with pneumococcal pneumonia or bacteremia, suggesting that these cells are engaged in the in vivo immune response (10). Furthermore, it has been demonstrated that peripheral blood mononuclear cells (PBMCs) from healthy adults living in a region with a high incidence of pneumococcal carriage and disease respond to pneumococcal antigens with both IFN-␥ and IL-17 production, indicating that exposure to pneumococci results in T cell-mediated immunological memory (25).…”
mentioning
confidence: 99%
“…T and B lymphocytes were found to be attracted to the site of infection, and the absence of PLY caused overall reduced bacterial growth as well as reduced recruitment of lymphocytes in vivo (376). A clinical study of CD4-positive T cells from previously exposed people showed that PLY, although not immunodominant, causes a distinct proinflammatory, Th1 profile of high IFN-␥, IL-12, and IL-17 levels and low IL-10 and IL-13 levels (377).…”
Section: Adaptive Immune Responses To Pftsmentioning
confidence: 99%
“…Pneumolysin has been described to activate innate immune cells by signalling through the NLRP3 inflammasome complex 34, resulting in a proinflammatory response that may attract pneumococcal ‐ specific T cells 35, and induce the development and activation of protective Th17 responses, in particular in the nasopharynx 36. While a few studies have reported on pneumolysin‐specific Th1 and Th17 responses in peripheral blood, these responses seem less apparent than responses in nasopharynx‐associated lymphoid tissue 21, 37. We postulate that, particularly in the neonatal period, the innate immune signalling properties ascribed to pneumolysin may predominate over that of T cell responses.…”
Section: Discussionmentioning
confidence: 99%